A GENETIC STUDY OF IRANIAN POPULATIONS: RED CELL ENZYMES - P. Amirshahi; D.D.Farhud; E. Sunderland; Sh. Tavakoli; P. Daneshmand (Tehran University of Medical Sciences, 1989)
A total of 1695 blood samples collected from ten ethnically distinct populations of Iran (Turks and Kurds of Rezaieh, Lurs, Aabolis, Baluchis, Turks and Kurds of Shrvan, Zoroastrians, Tehranis, and Kermanis) were examined for six polymorphic red cell enzyme systems, namely red cell acid phosphatase (AP), adenylate kinase (AK), phosphoglucomutase (PGM1), esteraxe D (ESD), adenosine deaminase (ADA), and 6-phosphogluconate dehydrogenase (6-PGD). The gene frequencies obtained from these samples were combined with the hitherto reportec corresponding data from other Iranian groups to determine the genetic structure of the Iranian population as a whole. The population of Iran was then compared with reported frequencies for neighbouring populations, as with those for European and Indian groups. The generalized feature of red cell enzyme gene frequencies for the whole country f about 31% Pa ; 67% Pb ; 2% Pc ; 6% Ak2 ; 31% PGM2 ; from the values found in the countries to the west and an approach to those in the Indian region.